Gut microbiome composition influences immunologic alterations in the blood and gut of HIV-positive and HIV-negative men who have sex with men - Neff, Charles Preston; Siebert, Janet; Karr, Mallory; Lippincott, Ricky; Kvaal, Rachel; Noe, Amy T.; Wall, Elena; Nusbacher, Nichole; Fiorillo, Suzanne; Fennimore, Blair P.; Campbell, Thomas B.; Lozupone, Catherine; et al. (Frontiers in Immunology, 2026)
BackgroundHIV infection and factors associated with sexual activity among men who have sex with men (MSM) can dysregulate relationships between the gut microbiome and immune system.MethodsTo explore these relationships in depth, blood and colonic biopsy samples from HIV+ and HIV- MSM and non-MSM were analyzed using Cytometry by Time of Flight (CyTOF). Immune profiles were then integrated with gut microbiome composition and MSM-related behaviors. ResultsHIV infection status influenced immune cell composition in colonic biopsies, marked by a loss of CD4⁺ CD103⁺ and CD8⁺CD103⁺ tissue-resident T cells and group 3 innate lymphoid cells (ILC3s). In the blood, HIV status was linked to reductions in circulating group 2 innate lymphoid cells (ILC2s), and naïve CD8⁺ T cells, while mucosal-associated invariant T (MAIT) cells were reduced in MSM engaging in high-risk sexual behaviors regardless of HIV status. Network analysis revealed distinct, tissue-specific relationships between immune cell populations and gut microbial taxa, further shaped by both HIV infection and MSM-associated factors. ConclusionsThese findings provide new insights into host:microbe interactions, with implications for immune regulation, HIV persistence, and transmission among MSM.